Posterior segment intraocular foreign body with secondary retinal detachment in a phakic eye: a case report - Dr. Amit C Porwal; Dr. Hardik Jain; Dr. Pratik Mahajan (International Journal of Medical Research and Review, 2020)
Intraocular foreign bodies (IOFBs) are an important cause of visual loss. The current case describes a case of retained intraocular foreign body with secondary retinal detachment in a phakic eye in a 38-year-old man. The foreign body was safely removed through the sclerotomy port without touching the crystalline lens. The current case report wanted to show the anatomic and visual outcomes of vitreoretinal surgery in such cases.